Alcohol Availability and Violence among Inner‐City Adolescents: A Multi‐Level Analysis of the Role of Alcohol Outlet Density - Bingham, C. Raymond (American journal of community psychology, 2010)
Researchers recognize that the connection between alcohol and peer violence may relate to community level ecological factors, such as the location of businesses that sell alcohol. Building on previous research among adults, this study examines the relationship between alcohol outlet density and violent behaviors among adolescents, taking into account demographic characteristics, individual alcohol use, and neighborhood level socioeconomic indicators. Data drawn from a diverse Emergency Department based sample of 1,050 urban adolescents, combined with tract level data from the state liquor control commission and U.S. Census, were analyzed. Results of multivariate multi‐level regression analysis indicate that alcohol outlet density is significantly related to adolescents' violent behaviors, controlling for demographic characteristics and individual alcohol use. Census tract level socioeconomic indicators were not significantly associated with youth violence. Findings suggest that alcohol outlet density regulation should be considered as part of broader violence prevention strategies for urban adolescents.Peer Reviewedhttp://deepblue.lib.umich.edu/bitstream/2027.42/117032/1/ajcp9353.pd